ETOS KERJA QUR’ANI DAN RELEVANSINYA TERHADAP ETOS KERJA SEKUNDER DALAM KONTEKS DUNIA KERJA MODERN - Zaskia (PT. Saha Kreasi Indonesia, 2025)
This article aims to examine the concept of work ethic from the perspective of the Qur'an, with an emphasis on its relevance to the formation of a secondary work ethic in the context of the modern workplace. The phenomenon of declining work ethic, such as weak discipline, low responsibility, and reduced professional integrity, is an important background to this study. Amidst the demands of professionalism, efficiency, and increasingly structured work systems, an ethical foundation is needed to maintain a balance between performance achievement and moral values. This study uses a qualitative method with a literature review approach, with data sources in the form of the Qur'an, tafsir books, Islamic thought books, as well as relevant articles and scientific journals. The data were analyzed using a thematic approach to identify Qur'anic work ethic values and their relationship with secondary work ethics. The results of the study show that the Qur'an views work as a mandate and worship that must be carried out professionally, honestly, and responsibly. Qur'anic values such as trust, itqan, honesty, and accountability are in line with the principles of secondary work ethic that emphasize discipline, performance evaluation, and compliance with work systems. This study concludes that the integration of Qur'anic work ethic with secondary work ethic is a conceptual solution in building a productive, integrity-based, and meaningful work culture in the modern era.